RS10455872 POLYMORPHISM WITHIN THE LPA GENE IS ASSOCIATED WITH SEVERE BIOPROSTHETIC MITRAL VALVE CALCIFICATION - Хуторная, Мария Владимировна; Понасенко, Анастасия Валериевна; Кутихин, Антон Геннадьевич; Рутковская, Наталья Витальевна; Цепокина, Анна Викторовна; Кондюкова, Наталья Владимировна; Южалин, Арсений Евгеньевич; Барбараш, Леонид Семенович (Medicine in Kuzbass, 2016)
Background. Bioprosthetic mitral valves frequently undergo severe calcification causing bioprosthetic valve failure, an urgent problem in cardiovascular surgery. However, no research has been performed on genetic susceptibility to severe bioprosthetic mitral valve calcification.Aim – to assess whether inherited variation in genes of lipid metabolism is associated with severe bioprosthetic mitral valve calcification.Materials and methods. We recruited 124 consecutive patients who underwent mitral valve replacement surgery. We assessed six polymorphisms within the four genes: rs1042031 and rs6725189 (APOB gene), rs7412 and rs429358 (APOE gene), rs1800588 (LIPC gene) and rs10455872 (LPA gene). To perform an additional quality control step, we tested six non-relevant polymorphisms within the genes encoding coagulation factors and integrin beta 3, a protein responsible for platelet aggregation: rs1799963 (F2 gene), rs6025 and rs6027 (F5 gene), rs6046 (F7 gene), rs5985 (F13A1 gene) and rs5918 (ITGB3 gene). Genotyping was carried out in 96-well format using the TaqMan SNP genotyping assay.Results. A/A genotype of the rs10455872 polymorphism within the LPA gene was associated with more than 5-fold increased risk of severe bioprosthetic mitral valve calcification compared to the A/G genotype.Conclusion. Polymorphisms within the lipid metabolism genes may be associated with severe bioprosthetic mitral valve calcification.
Keywords: bioprosthetic heart valves; calcification; lipid metabolism; lipoprotein(a); genetic susceptibility